ANALISIS RONA LINGKUNGAN KAMPUS IAIN SYEKH NURJATI CIREBON DALAM MEWUJUDKAN KAMPUS BERBASIS KONSEP GREEN CAMPUS - Ina Rosdiana Lesmanawati (Holistik, 2012)
This study aims to determine the quality of the campus environment IAIN Sheikh Nurjati Cirebon for realizing the campus based on the concept of green campus. This study uses a quantitative approach using a survey method. Samples taken from 5200 was 260 academicians campus. Aspects investigated are the perception of the campus community to the concept of green campus, campus map building, and diversity of plants in the green belt around the campus. The results of this study indicate that: first, community college still think IAIN Sheikh Nurjati is not categorized as the green campus yet. Second, the balance between building size with a green open space (RTH) is not in accordance with existing regulations and still more land sleep. Third, the number of plant species is quite a lot, but the species is still not sufficient, and campus area is still hot.